Subwavelength-engineered metamaterial devices for integrated photonics - Sánchez-Postigo, Alejandro; Ginel-Moreno, Pablo; Pereira-Martín, Daniel; Hadij-El-Houati, Abdelfettah; Luque-González, José Manuel; Pérez-Armenta, Carlos; Wanguemert-Pérez, Juan Gonzalo; Ortega-Moñux, Alejandro; Halir, Robert; Schmid, Jens H.; Soler-Penades, Jordi; Nedeljkovic, Milos; et al. (My University, 2022)
The engineering of subwavelength grating metamaterials has become an essential design strategy in silicon photonics. The lithographic segmentation of integrated waveguides at the subwavelength scale enables the synthesis of on-chip metamaterials and provides control over optical properties such as mode delocalization, wavelength dispersion, and anisotropy. At the near-infrared wavelengths of the 1.55-μm telecom band, a range of subwavelength-based devices with unprecedented performance has been demonstrated, including couplers, filters, and polarization-handling structures. In this invited paper, we review the foundations of anisotropic subwavelength grating metamaterials and discuss our latest advances in five new subwavelength-enhanced devices: a millimeter-long optical antenna that is evanescently coupled to diffractive lateral segments, thereby achieving a record far-field beam width of 0.1º in silicon; a multi-line integrated Bragg filter also using lateral loading segments, which produces 20 non-uniformly spaced spectral notches with a 3-dB linewidth as low as 210 pm; a low-loss curved wavelength demultiplexer; a segmented multi-mode interference coupler based on novel bricked subwavelength gratings, yielding a 1-dB bandwidth exceeding 140 nm; and a suspended waveguide platform with low propagation loss at mid-infrared wavelengths.
Keywords: Metamateriales; Fotónica; Silicon photonics; Integrated optics; Subwavelength gratings; Metamaterials; Near-infrared; Mid-infrared; Waveguides; Off-chip couplers